2017
DOI: 10.1039/c7ra06232j
|View full text |Cite
|
Sign up to set email alerts
|

A novel microporous amorphous-ZnO@TiO2/graphene ternary nanocomposite with enhanced photocatalytic activity

Abstract: Configuration model of the amorphous-TiO2/RGO heterostructure and the photocatalytic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The crystallinity and size of networked TiO 2 NPs are consistent throughout all aerogel variations with anatase being the dominant crystal phase as noted by the (101) X-ray diffraction (XRD) peak at 25.3°. The aerogels also contain a minimal amount of amorphous TiO 2 , indicated by the broad feature spanning 25°–35° , and brookite polymorph noted by the small (121) feature at 30.9° (Figure b). The presence of Au is detected by diffraction peaks for Au(111) at 38.1°, which overlaps with some anatase facets, and Au(200) at 44.3°. , As the weight loading increases and particles grow, the Au features become more prominent (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The crystallinity and size of networked TiO 2 NPs are consistent throughout all aerogel variations with anatase being the dominant crystal phase as noted by the (101) X-ray diffraction (XRD) peak at 25.3°. The aerogels also contain a minimal amount of amorphous TiO 2 , indicated by the broad feature spanning 25°–35° , and brookite polymorph noted by the small (121) feature at 30.9° (Figure b). The presence of Au is detected by diffraction peaks for Au(111) at 38.1°, which overlaps with some anatase facets, and Au(200) at 44.3°. , As the weight loading increases and particles grow, the Au features become more prominent (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, more electron–hole pairs are generated which are effectively separated due to the strong interfacial interaction, band bending alignment, and changes in the quasi-Fermi energy level at the core–shell (n/n) heterojunction . Furthermore, adsorption and surface reactions on the amorphous TiO 2 shell are easier than those on pure crystalline surfaces, which further enhances the charge separation by passivating the ZnO NWs surface. Shalom et al have shown the improved performance of CdS QD-sensitized mesoporous solar cells after the thin coating of an amorphous TiO 2 . In addition, the TiO 2 coating significantly reduces the recombination of electron and holes arising on the surface of ZnO NWs, as evidenced by PL results.…”
Section: Resultsmentioning
confidence: 99%
“…A novel microporous amorphous-ZnO@TiO 2 heterostructure was created by Guo and colleagues, featuring outstanding attributes, such as high surface area (336 m 2 g −1 ), superior mobility of charge carriers, and increased photocatalytic efficiency. 224 In a related work, Bai and colleagues confirmed that amorphous manganese oxides (a-MnO x ) demonstrated superior photoinduced ORR/OER bifunctional catalytic performance compared to crystalline manganese catalysts owing to the high defect state of a-MnO x with surface-exposed catalytic active sites and abundant edge active sites. 225 Hence, amorphous inorganics are promising materials for utilization in photocatalysis reactions and photoconversion devices.…”
Section: Catalytical Materialsmentioning
confidence: 97%